Humoral and cellular immune response in patients with hematological disorders after two doses of BNT162b2 mRNA COVID‐19 vaccine: A single‐center prospective observational study (NCT05074706). Issue 4 (30th August 2022) - Bossi, Elisa; Aroldi, Andrea; Borin, Lorenza Maria; Verga, Luisa; Fontana, Diletta; Cocito, Federica; Manghisi, Beatrice; Rindone, Giovanni; Cavalca, Fabrizio; Ripamonti, Alessia; Raggi, Monica; Malandrin, Sergio Maria Ivano; et al.
Abstract: Hematological patients at higher risk of severe COVID‐19 were excluded from the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) vaccine trials. In this single‐center observational prospective study (NCT05074706), we evaluate immune response in the hematological patients followed at the Hematological Division of San Gerardo Hospital, Monza (Italy) deemed to be severely immunosuppressed after vaccination with two doses of the BNT162b2 vaccine. Anti‐SARS‐CoV‐2 immunoglobulin G titers above the cutoff value of 33.8 BAU/ml were detected in 303 (80.2%) out of the 378 patients enrolled. Patients with lymphoproliferative disorders had a significant lower probability of immunization (43.2% vs. 88.4%, p < 0.001). Patients treated with anti‐CD20 showed a significantly lower probability of immunization compared to all other treatments (21.4%, p < 0.0001). Among 69 patients who failed seroconversion, 15 patients (22.7%) showed a positive T‐cell response. Patients previously treated with anti‐CD20 were 2.4 times more likely to test positive for T‐cell responses ( p = 0.014). Within a follow‐up of 9 months from the second COVID‐19 vaccination, symptomatic SARS‐CoV‐2 infections were reported by 20 patients (5.3%) and four of them required hospitalization. Successful serological or T‐cell‐mediated immunization conferred protection from symptomatic COVID‐19. Patients treated with anti‐CD20 who were not seroconverted after vaccination might still be protected from COVID‐19 due to the T‐cell immune response.